Evaluation of the effect of knots on rolling shear strength of cross laminated timber (CLT). (20th October 2019) - Cao, Yawei; Street, Jason; Li, Minghao; Lim, Hyungsuk
Highlights: Knots would not decrease rolling shear strength of cross laminated timber. Knot presence affects rolling shear failure mechanisms. Two-plate shear test can be used to evaluate effects of laminations' heterogeneity. Short-span bending test is more conservative than two-plate shear test. Abstract: The study experimentally and analytically investigated the effect of knots on the rolling shear (RS) strength of 3-ply southern yellow pine cross-laminated timber (CLT). Center-point bending tests and two-plate shear tests were conducted on six CLT configurations composed of different types of cross layer laminations based on knots conditions (No Knots, Sound Knots, and Decayed Knots) and pith conditions (Pith, No Pith). The shear analogy method was implemented to evaluate the RS strength values from the bending test results, which were compared against the results from the two-plate shear tests. The cross-layer laminations with either sound knots or decayed knots improved the RS strength of CLT. In general, the RS predicted by the shear analogy method was conservative.